BIMBINGAN PRAKTIK SALAT UNTUK SISWA BERKEBUTUHAN KHUSUS DI SMP - Sulfiyah Sulfiyah (IAIN Purwokerto, 2018)
Abstract: One of national education aim is to developing student’s potentials in order to become a faithful man. It is based on Republic of Indonesia’s Law Number 20 of 2003 on National Education System, Chapter II Article 3. Islamic Religious Education is one of education that done to create a faithful man. Prayer is one of Islamic Religious Education’s matter should be learned by all Moslem’s students, include students with special needs. Research of prayer practice guidance is an important thing to be done. The important thing should be researched is about prayer practice that taught in the inclusion school. Inclusion school have regular (common) students and special needs students. How the teacher can teach prayer practice for students with special needs in the inclusion school. Once of inclusion school is Junior High Boarding School Putra Harapan. The goal of this research is to explore and to describe about how teacher guides prayer practice for students with special needs in Junior High Boarding School Putra Harapan Purwokerto Banyumas. This research belongs to field research on qualitative descriptive form. The methods of collecting data used by the author are interview, observation and documentation. Meanwhile to analyze of data, it’s done by collecting data, reducing, presenting and verifying data to be valid and reliable report. The findings of this research show that guidance of prayer practice for students with special needs in Junior High Boarding School Putra Harapan done through some ways namely dividing students into two class that regular and inclusion class, establishing guidance of prayer practice program, using musyafahah and demonstration methods. Key words: guidance, prayer practice, students with special needs.